Islam dan Sekularisasi Politik di Indonesia - Mohamad Latief (Universitas Darussalam Gontor, 2017)
Throughout Indonesia’s independence history, discourse on secularization of politics arises constantly and draws a widespread appeal from many researchers. Conceptual issues pertaining to separation between Islam and state (secularism) and how it is realized, have been able to make the secularization of politics one of the most dynamic objects of research and directly reach the socio-political reality of the Indonesians. In the pluralistic society, quandaries emerge oftentimes as to make the religious and nationalist commitments converge. Even though inseparable, the government frequently designates Islam as opposing to nationalism. Islam has been charged with a symbol of exclusivism and anti-diversity. Islam has even been regarded as the second political enemy after communism and thus requires its elimination. This is hence the pretext for imposing the secularization. Islam is consequently separated from political concern and its adherents are discarded from any policy-making process. This article seeks to both elucidate the secularization and analyze its propagation in Indonesia spanning the time prior to its independence until the present time. In this section, the articles finds out that secularization in Indonesia proceeds as a top-down movement enforced by the ruling towards the ruled; the Muslim society. In the following section, the article also discloses deficiency in the secularization and exposes a groundwork for its impending failure. In reference to the secularization project in Turkey, the article reveals that separation of Islam and state in Indonesia falls short due to absence of support from the Muslim grass-root.